A Multi‐Level Theoretical Study to Disclose the Binding Mechanisms of Gold(III)–Bipyridyl Compounds as Selective Aquaglyceroporin Inhibitors. Issue 55 (7th September 2017) - Graziani, Valentina; Marrone, Alessandro; Re, Nazzareno; Coletti, Cecilia; Platts, James A.; Casini, Angela
Abstract: Structural studies have paved the avenue to a deeper understanding of aquaporins (AQPs), small ancient proteins providing efficient transmembrane pathways for water, small uncharged solutes such as glycerol, and possibly gas molecules. Despite the numerous studies, their roles in health and disease remain to be fully disclosed. The recent discovery of Au III complexes as potent and selective inhibitors of aquaglyceroporin isoforms paves the way to their possible therapeutic application. The binding of the selective human AQP3 inhibitor, the cationic complex [Au(bipy)Cl2 ] + (Aubipy), to the protein channel has been investigated here by means of a multi‐level theoretical workflow that includes QM, MD and QM/MM approaches. The hydroxo complex was identified as the prevalent form of Aubipy in physiological media and its binding to AQP3 studied by MD. Both non‐covalent and coordinative Aubipy–AQP3 adducts were simulated to probe their role in the modulation of water channel functionality. The electronic structures of representative Aubipy–AQP3 adducts were then analysed to unveil the role played by the metal moiety in their stabilisation. This study spotlights the overall importance of three key aspects for AQP3 inhibition: 1) water speciation of the Au III complex, 2) stability of non‐covalent adducts and 3) conformational changes induced within the pore by the coordinative binding of Au III . The obtained results are expected to orient future developments in the design of isoform‐selective Au III inhibitors. Abstract : AQP3 inhibition —a "golden" recipe for selective AQP3 inhibition through aquation, stacking and coordination (see figure). The inhibition of human AQP3 by [Au(bipy)Cl2 ] + by binding to the protein channel has been investigated by QM, MD and QM/MM approaches, probing the modulation of the water channel functionality.